Protection against lung pathology during obesity-accelerated ageing in mice by the parasitic worm product ES-62 - Harnett, Margaret M.; Lumb, Felicity E.; Crowe, Jenny; Doonan, James; Buitrago, Geraldine; Brown, Stephanie; Thom, Gillian; MacDonald, Amy; Suckling, Colin J.; Selman, Colin; Harnett, William (Frontiers in Immunology, 2023)
Mice develop pathology in the lungs as they age and this may be accelerated by a high calorie diet (HCD). ES-62 is a protein secreted by the parasitic worm Acanthocheilonema viteae that is immunomodulatory by virtue of covalently attached phosphorylcholine (PC) moieties. In this study, we show that weekly treatment of C57BL/6j mice with ES-62 protected against pathology in the lungs in male but not female mice fed a HCD from 10 weeks of age as shown by reductions in cellular infiltration and airway remodelling, particularly up to 160 days of age. ES-62 also reduced gene expression of the cytokines IL-4 and IL-17 and in addition the TLR/IL-1R adaptor MyD88, in the lungs of male mice although HCD-induced increases in these inflammatory markers were not detected until between 340 and 500 days of age. A combination of two drug-like ES-62 PC-based small molecule analogues, produced broadly similar protective effects in the lungs of male mice with respect to both lung pathology and inflammatory markers, in addition to a decrease in HCD-induced IL-5 expression. Overall, our data show that ES-62 and its SMAs offer protection against HCDaccelerated pathological changes in the lungs during ageing. Given the targeting of Th2 cytokines and IL-17, we discuss this protection in the context of ES-62's previously described amelioration of airway hyper-responsiveness in mouse models of asthma.